Analysis of influence factors of customer loyalty under e-commerce environment. (18th August 2018) - Xiong, Yueming; Zhang, Yanyu
Abstract: Whether in physical commerce environment or e-commerce environment, cultivating and maintaining customer loyalty is the key factor for enterprises to make profits. How to systematically construct customer relationship and effectively enhance customer loyalty is an important problem that online stores must face in the e-commerce environment. This paper points out the rational and active features of the online customer loyalty. Based on the above analysis, the index system of influence factors of customer loyalty under e-commerce environment is given, which involves three first-level indicators (index of behaviour, attitude and affection) and twelve second-level indicators (number of repeat purchases, frequency of repeat purchases, number of recommendation to other customers, communication time with the customer service, time conversion cost, economic conversion cost, sensitivity degree to the price, premium ability, privacy protection, business reputation, perceived service quality, perfection degree of credit system). The weight of each index is given according to Entropy Method.